(untitled) (Politeja, 2022)
The article is the first attempt at describing and comparing leaders of four most important populist groupings in Poland: Samoobrona, PiS, LPR, Kukiz’15. It makes three primary contributions to the literature of the subject. In its theoretical aspect, it shows that the literature concerning the analysed issue is still at the stage of being developed. When it comes to the analysis of data, it was found that populist party leaders played an important political role in Poland. In the case of Samoobrona, PiS and Kukiz’15 they played a key role in the process of origination of their parties, while in PiS they still hold a very strong intra-party position.